SAE Technical Paper Series 2019
DOI: 10.4271/2019-24-0172
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Efficiency Comparison of Different Injector Constellations in a CI Engine

Abstract: More stringent emission regulations call for high-efficiency engines in the heavy-duty vehicle sector. Towards this goal, reduced heat losses, as well as increased work output, are needed. In this study, a multiple injector concept to control the combustion as well as reduce the hot boundary zones is proposed. Earlier studies have proven that multiple injectors experience lower heat losses and higher efficiency. However, a comprehensive investigation of the causes for experimental heat loss was not performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…However, the increased exhaust energy, rendering work in the DCEE waste-heat recovery (WHR) system, improves the two-injector MF values. This is in line with previous studies [9,10,13]. Thus, the MF value remains sensitive to the WHR efficiency, where a higher efficiency favors the two-injector cases.…”
Section: Merit Functionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the increased exhaust energy, rendering work in the DCEE waste-heat recovery (WHR) system, improves the two-injector MF values. This is in line with previous studies [9,10,13]. Thus, the MF value remains sensitive to the WHR efficiency, where a higher efficiency favors the two-injector cases.…”
Section: Merit Functionsupporting
confidence: 92%
“…High heat losses further follow in other engine concepts due to the current trend towards higher compression ratios giving higher incylinder temperatures [7,8]. To tackle this challenge, studies have suggested that multiple injectors reduce heat losses while keeping emissions at decent levels [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, further efficiency increases are possible. Similarly, the enhanced mixing by an increased number of injector holes is reported to decrease soot and NOx levels in addition to reduced heat losses [11]. Thus, this concept diminishes the NOx-soot-efficiency trade-off.…”
Section: Introductionmentioning
confidence: 96%
“…The latter advantages make the isobaric combustion suitable for split-cycle concepts such as the double compression expansion engines (DCEE) concept [15][16][17], which has the potential to achieve BTE up to 56%. Numerical and experimental work has shown that the use of multiple injectors can reduce the soot emission, while still achieving the desired isobaric combustion [13,18,19]. The advantage of multiple injectors provides flexibility in the temporal and spatial control of fuel sprays avoiding the injection into the burnt zone and hence reducing the soot emissions along with enhanced mixing.…”
Section: Introductionmentioning
confidence: 99%